2012
DOI: 10.1016/j.resuscitation.2012.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Differences in outcomes between ICU attending and senior resident physician led medical emergency team responses

Abstract: Introduction Although rapid response systems (RRS) have been shown to decrease the incidence of cardiac arrest (CA), there are no studies evaluating optimal staffing. We hypothesize that there are no outcome differences between ICU physician and senior resident led events. Methods A retrospective study of the RRS database at a single, academic hospital was performed from July 1, 2006 to May 31, 2010. Surgical patients and those in the ICU were excluded. Daytime (D) was defined as 7 am–5 pm Monday through Fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 11 publications
1
35
1
1
Order By: Relevance
“…(13)(14)(15)(16)(17) The teams were mostly composed of doctors, nurses, and physical therapists with experience and/ or specialization in critical care. (13)(14)(15)(16)(17)(18)(19)(20) Some studies included a pharmacist, laboratory technicians, radiology technicians, and administrators and clinical secretaries. (13,(16)(17)(18)20) It was shown that the presence of a resident doctor in the team represented no difference when compared with the responsible intensivist.…”
Section: Composition And/or Capacity Building Of Teamsmentioning
confidence: 99%
See 3 more Smart Citations
“…(13)(14)(15)(16)(17) The teams were mostly composed of doctors, nurses, and physical therapists with experience and/ or specialization in critical care. (13)(14)(15)(16)(17)(18)(19)(20) Some studies included a pharmacist, laboratory technicians, radiology technicians, and administrators and clinical secretaries. (13,(16)(17)(18)20) It was shown that the presence of a resident doctor in the team represented no difference when compared with the responsible intensivist.…”
Section: Composition And/or Capacity Building Of Teamsmentioning
confidence: 99%
“…(13)(14)(15)(16)(17)(18)(19)(20) Some studies included a pharmacist, laboratory technicians, radiology technicians, and administrators and clinical secretaries. (13,(16)(17)(18)20) It was shown that the presence of a resident doctor in the team represented no difference when compared with the responsible intensivist. (16) Capacity building and maturation of the teams can improve the outcomes, reducing mortality and unplanned ICU admissions as well as enabling shorter activation time for efferent teams.…”
Section: Composition And/or Capacity Building Of Teamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of our staffing variables such as board certification and participation in daily care plans are components of the Leapfrog ICU staffing criteria [34]. Prior research on RRTs and ICU care transitions suggest that RRT team composition [35,36] and ICU liaison nurses (defined as dedicated registered nurses [RNs] who aid in post-ICU care transitions) might impact patient outcomes [37]. Trauma center status has also been shown to impact FTR [31,38] and is reflective of patient case mix at a given hospital [39].…”
Section: Survey Instrumentmentioning
confidence: 99%